Jet properties in PbPb and pp collisions at $ \sqrt{s_{\mathrm{N}\;\mathrm{N}}}=5.02 $ TeV - CMS collaboration (2303 authors); Nayak, Aruna; Bargassa, Pedrame; Beirão Da Cruz E Silva, Cristóvão; Di Francesco, Agostino; Faccioli, Pietro; Galinhas, Bruno; Gallinaro, Michele; Hollar, Jonathan; Leonardo, Nuno; Lloret Iglesias, Lara; Seixas, Joao; et al. (My University, 2018)
Modifications of the properties of jets in PbPb collisions, relative to those in pp collisions, are studied at a nucleon-nucleon center-of-mass energy of $ \sqrt{s_{\mathrm{N}\,\mathrm{N}}}=5.02 $ TeV via correlations of charged particles with the jet axis in relative pseudorapidity (Δη), relative azimuth (Δϕ), and relative angular distance from the jet axis $ \varDelta \mathrm{r}=\sqrt{{\left(\varDelta \eta \right)}^2+{\left(\varDelta \phi \right)}^2} $ . This analysis uses data collected with the CMS detector at the LHC, corresponding to integrated luminosities of 404 μb$^{−1}$ and 27.4 pb$^{−1}$ for PbPb and pp collisions, respectively. Charged particle number densities, jet fragmentation functions, and jet shapes are presented as a function of PbPb collision centrality and charged-particle track transverse momentum, providing a differential description of jet modifications due to interactions with the quark-gluon plasma.